ANALISIS VISUAL DESAIN KARAKTER FAUST PADA GAME “MY LOVELY DAUGHTER” MENGGUNAKAN METODE MANGA MATRIX - Fitriadi Putri, Tiara Andhienia (Wimba : Jurnal Komunikasi Visual, 2024)
Video games are a popular entertainment phenomenon among people today. Various genres of video games have sprung up and have their own impression on the players. In it, video games have visual elements that have their own uniqueness and aesthetic value. These visuals can provide information, especially on character design in the game world. Like the visual elements in the game "My Lovely Daughter", where the visual elements in it have meaning to each other and form a narrative in the game itself. Characters that are created with certain characteristics will attract the attention of players. The purpose of this research is to interpret each visual element in the character and how important character design is to build the identity of a game characteristic using the manga matrix method. Through the analysis, the visual elements of the character design in the game show that the design references chosen for the Faust character have been carefully considered, from the face, clothes, accessories to the personality part of the character.